PENGEMBANGAN BUKU SAKU MATEMATIKA BERBASIS PROBLEM SOLVING PADA MATERI BENTUK ALJABAR SISWA KELAS VIII SMPN 13 MERANGIN - Pitri Yanti; Hidayati Rais; Sukur (Hira Institute, 2024)
This research is research and development (R&D) which aims to produce a mathematics pocket book that is valid, practical and effective. The development model used is 4D. This problem-solving-based mathematics pocket book was validated by 5 material, language and media expert validators. The product validator from the research results is known from the validation sheet, Practicality using a practicality questionnaire instrument and student interview sheets about product practicality. Meanwhile, effectiveness is seen from student activities and student learning outcomes. The results of data analysis show that the average validation score for material experts is 4.7 in the very valid category, Indonesian language experts are 4.6 in the very valid category, media experts are 4.78 in the very valid category, and teacher validation is 4. 87 in the very valid category. very valid. The average overall validator score is 4.74 in the very valid category. The percentage of responses to the practicality questionnaire was 83.75% in the very practical category. The average percentage of student activity was 89.85% in the very effective category and the percentage of effectiveness in learning outcomes was 80.8% in the effective category. It can be concluded that the problem solving-based mathematics pocket book developed is valid, practical and effective. A mathematics pocket book based on problem solving can be used in the mathematics learning process of algebra material for class VIII students. The distribution was given to mathematics teachers and all class VIII students